Attitude Of Adolescents Towards Their Social Life in Urban Slum of Asarwa, Ahmedabad - A Community Based Cross Sectional Study - Minal S Gadhavi; Rajshree Bhatt; Pritesh G Patel; K N Sonaliya; Chintul Shah; H K Mehta (Medsci Publications, 2012)
Background: Adolescence (10-19years of age) is a period of rapid transition in life from "childhood" to "Adulthood". This is very turbulent and crucial developmental phase, during which the adolescent experiences physical, emotional, spiritual and moral changes. This study aims on these changes. Methodology: A cross sectional study was conducted in the month of March 2009 at Asarwa slums in Ahmedabad. The information was gathered in pretested performa by one to one interview, taking in account the gender specification. Results: We surveyed 257 adolescents, among them 62(24.12%) were male and 95 (75.88%) were female (M:F= 0.65:1) ,with mean age 15.85 years.More than half of the adolescents were secondary educated 136 (52.92%) and 11 (4.28%) were illiterate. Adolescents who were found positive in their attitude in adverse situation in life were 67%. 198(77.04%) adolescent were respectful towards their elders only few were hesitated (8.56%). Adolescents who thought that family restriction was good for them were 138 (53.7%). In our study 30% shows shyness towards the physical changes in their body. In present study 83 (32.30%) adolescent were angry with their failure in life. Among the surveyed group19 (30.67%) male and 5(2.50%) female were addicted to various form of tobacco. Conclusion: Attitute of adolescent is positive in adverse situation of life. They respect elders. However they feel angry about their future. Addiction rate is higher among male adolescent.